Relationship of upflowing ion beams and conics around the dayside cusp/cleft region to the interplanetary conditions - W. Miyake; W. Miyake; T. Mukai; N. Kaya (Annales Geophysicae, 2002)
The dayside cusp/cleft region is known as a major source of upflowing ionospheric ions to the magnetosphere. Since the ions are supposed to be energized by an input of energy from the dayside magnetospheric boundary region, we examined the possible influence of the interplanetary conditions on dayside ion beams and conics observed by the polar-orbiting Exos-D (Akebono) satellite. We found that both the solar wind velocity and density, as well as IMF By and Bz , affect the occurrence frequency of ion conics. The energy of ion conics also depends on the solar wind velocity, IMF By and Bz . The ion beams around the local noon are not significantly controlled by the interplanetary conditions. The results reveal that ion convection, as well as the energy source, is important to understand the production of dayside ion conics while that of ion beams basically reflects the intensity of local field-aligned currents. Key words. Ionosphere (particle acceleration) – magnetospheric physics (magnetopause, cusp, and boundary layers; magnetosphere ionosphere interaction)